From Algorithmic Logic to Pneumatological Presence : A Theological and Statistical Discernment of AI in the FJKM Homiletic Context - Nomenjanahary Jenny Patrick; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2026)
The rapid integration of generative artificial intelligence (AI) into homiletic and liturgical practices marks a